Scalable Synthesis of a Sub-10 nm Chalcopyrite (CuFeS2) Nanocrystal by the Microwave-Assisted Synthesis Technique and Its Application in a Heavy-Metal-Free Broad-Band Photodetector - Kumar, B.; Singh, S.V.; Chattopadhyay, A.; Biring, S.; Pal, B.N. (American Chemical Society, 2020)
A heavy-metal-free chalcopyrite (CuFeS2) nanocrystal has been synthesized via microwave-assisted growth. Large-scale nanocrystals with an average particle size of 5 nm are fabricated by this technique within a very short period of time without any need for organic ligands. Scanning electron microscopy study (SEM) of individual synthesis steps indicates that aggregates of nanocrystals are formed as flakes during microwave-assisted synthesis. The colloidal solution of the CuFeS2 nanocrystal was prepared by sonicating these flakes. Transmission electron microscopy (TEM) study reveals the growth of sub-10 nm CuFeS2 nanocrystals that are further characterized by X-ray diffraction. UV-visible absorption spectroscopic study shows that the band gap of this nanocrystal is ∼1.3 eV. To investigate the photosensitive nature of this nanocrystal, a bilayer p-n heterojunction photodetector has been fabricated using this nontoxic CuFeS2 nanocrystal as a photoactive material and n-type ZnO as a charge-transport layer. The detectivity of this photodetector reaches above 1012 Jones in visible and near-infrared (NIR) regions under 10 V external bias, which is significantly high for a nontoxic nanocrystal-based photodetector. Copyright © 2020 American Chemical Society.
Keywords: chalcopyrite; nanocrystal; Scalable Synthesis; a Sub-10 nm Chalcopyrite; Microwave-Assisted; Synthesis Technique